Analisis Perilaku Kerusakan Balok Beton Bertulang Pascabakar - Ricky Andriano; Reni Suryanita; Ismeddiyanto Ismeddiyanto (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
The current building structure cannot be separated from the risk of fire. So that a research is needed to study the impact of fire hazard on building structures. The purpose of this research is to analyze the form of damage that occurs on reinforced concrete (RC) beam after experiencing a fire. The test specimens used are RC beam with the cross section size 10 x 20 cm and with the length of span of 125 cm. The concrete strength planned in this study is 20 MPa. The combustion process was carried out in a local brick factory furnace with a fire duration of 30 minutes and 60 minutes. The results showed that there was a damage the RC beam in the form of cracks, spalling, and discoloration. The width of the crack measured in RC beam varying from 0.5 - 3 mm. It was also find that spalling width seen at RC beam was 10 cm, it was considend that these beam had been considered as desctructive. More over the color on the concrete surface changed to grayish white. The color changes indicated that the RC bem had been exposed to a temperatures between 600C-900C.Keyword : reinforced concrete beam, cracks, spalling, color change